John Stuart Mill e John Rawls: duas concepções de justiça em diálogo - Hoffmann, Henor Luiz dos Reis (Universidade do Vale do Rio dos Sinos, 2021)
The objective of this work is to make a comparison between the conceptions of justice of John Stuart Mill and John Rawls, starting from an exegesis of the main works of the authors. The dissertation is divided into three parts: (i) John Stuart Mill's Theory of Justice, (ii) John Rawls' Theory of Justice, (iii) Comparing: John Mill and John Rawls. The first part aims to reconstruct the Millian theory, in order to compare it with the Rawlsian theory. Based on the exegesis of Mill's main works, he is characterized as a non-teleological, but deontological, rule-utilitarian. He rejects a metaphysical conception of the person. The idea of the person and his moral psychology are the basis on which his principle of utility, understood in the broad sense, is anchored. Also in this chapter, we examine Millian social liberalism, that is, the priority defense of basic individual freedoms equated with social and economic justice. In the second chapter, dedicated to Rawls, we initially approach the thought experiment called the original position. Next, we consider the role of consequentialist elements in justice as fairness, followed by an analysis of the two principles of justice, equal freedom and equal opportunity. The climax of the present work is reached in the third chapter, as it is at this moment that we realize that there are more convergences than divergences between the two authors. Finally, in the final considerations, the similar and distinct aspects of the theories are weighed in the balance, reaching a verdict on which of the conceptions of justice has advantages over the other. We conclude that justice as fairness has advantages over Millian theory.
Keywords: Mill; Rawls; Pessoa; Liberdade; Justiça distributiva; People; Liberty; Distributive justice; ACCNPQ::Ciências Humanas::Filosofia